Business Actors' Understanding of Green Accounting and Its Impact on the Quality of Financial Reporting - Debora Rompas; Randy Chaidir; Eliska Gricy Lumempouw; Christania Graciella Angel (Cattleya Darmaya Fortuna, 2026)
This study aims to examine the effect of understanding and implementation on the quality of financial management among business actors. A quantitative approach was employed using a survey method with purposive sampling. Data were analyzed using multiple linear regression to test both partial and simultaneous effects among variables. Descriptive analysis indicates that the levels of understanding (mean = 3.84), implementation (mean = 3.62), and quality (mean = 3.75) fall within the high category. Regression results reveal that understanding has a positive and significant effect on quality (β = 0.482; t = 6.214; p < 0.001). Similarly, implementation also has a positive and significant effect on quality (β = 0.371; t = 4.987; p < 0.001). Simultaneously, both variables significantly influence quality (F = 105.62; p < 0.001), with a coefficient of determination (R²) of 0.570, indicating that 57% of the variance in quality is explained by understanding and implementation. These findings suggest that conceptual understanding plays a more dominant role than implementation in improving financial management quality, although both variables contribute significantly. This study implies that strengthening conceptual capacity and ensuring consistent financial practices are strategic factors in enhancing business management quality.